Knowledge gaps in Alzheimer's disease immune biomarker research. Issue 12 (13th May 2021) - Morgan, David G.; Mielke, Michelle M.
Abstract: Considerable evidence has accumulated implicating a role for immune mechanisms in moderating the pathology in Alzheimer's disease dementia. However, the appropriate therapeutic target, the appropriate direction of manipulation, and the stage of disease at which to begin treatment remain unanswered questions. Part of the challenge derives from the absence of any selective pressure to develop a coordinated beneficial immune response to severe neural injury in adults. Thus, immune responses to the prevailing stimuli are likely to contain both beneficial and detrimental components. Knowledge gaps include: (1) how a biomarker change relates to the underlying biology, (2) the degree to which pathological stage group differences reflect a response to pathology versus trait differences among individuals regulating risk of developing pathology, (3) the degree to which biomarker levels are predictive of subsequent changes in pathology and/or cognition, and (4) experimental manipulations in model systems to determine whether differences in immune biomarkers are causally related to pathology.